A nano titanium dioxide / porous carbon sphere material and its preparation method and application
By preparing nano-titanium dioxide/porous carbon ball materials, the problems of poor adsorption effect and narrow spectral response range of nano-titanium dioxide catalysts in photocatalytic oxidation technology are solved, and efficient visible light catalytic performance and stable use effects are achieved.
Patent Information
- Application Number
- CN202111663062.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-12-30
AI Technical Summary
In photocatalytic oxidation technology, nanotitanium dioxide catalysts have problems such as poor adsorption effect, high electron-hole recombination rate and narrow spectral response range, resulting in unsatisfactory catalytic effect.
Through the coordination and polymerization response of iron salt, carbonate derivatives and brachycal formal, the polymer front -drive body is obtained, and carbonization treatment of the gas atmosphere is prepared to prepare porous carbon ball materials. In the solvent thermal reaction, the porous carbon ball material reacts with the organic titanium compound to form nano -titanium dioxide/porous carbon ball material.
This method can obtain anatase nano-titanium dioxide with a high degree of crystallization without secondary roasting, and improves the visible light catalytic performance of the composite material through the co-doping of metal ions and non-metal ions. The excellent specific surface area and mesoporous structure of porous carbon sphere materials improve the enrichment ability of photocatalytic reactions and the conductivity of photoelectrons, and enhance the adsorption synergistic performance of the material.
Smart Images

Figure CN116408120B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nano titanium dioxide / porous carbon ball material and a preparation method and application thereof, and relates to the technical field of photocatalysis. Background Art
[0002] With the rapid development of industry, the situation facing the global ecological environment is becoming increasingly severe. In addition to water pollution, gas pollution emitted by production is more hidden and dangerous, posing a serious threat to human health and the ecological environment. Photocatalytic oxidation technology has the advantages of mild operating conditions and a wide range of treatment, and has developed into an emerging environmental purification technology. Cheap and non-toxic nano-titanium dioxide catalysts are one of the most valuable photocatalysts, but nano-titanium dioxide catalysts have the disadvantages of poor adsorption effect, high electron-hole recombination rate, and narrow spectral response range, which seriously reduce their catalytic effect.
[0003] Among the various modification methods for nano-titanium dioxide catalysts, the composite catalyst formed by immobilization loading can improve the catalytic effect while reducing the agglomeration of titanium dioxide, which is beneficial to the separation and recovery of the catalyst. Compared with other loading materials, carbon ball materials have the characteristics of high mechanical strength and good dispersibility. They can improve the adsorption of pollutants by composite materials and promote photoelectron transfer, while broadening the light response range of the material. In addition, they can effectively disperse and stabilize photoactive nanoparticles. The literature Carbon 2014 67:104–118 compares the photocatalytic oxidation degradation performance of composite materials obtained by depositing titanium dioxide nanoparticles on spherical activated carbon and random three-dimensional activated carbon. The spherical carbon / titanium dioxide composite material exhibits better ultraviolet photocatalytic performance when treating propylene, which is speculated to be due to the higher dispersion and coverage of the generated nano-titanium dioxide on the spherical material, and the higher crystallinity of the anatase type. The literature Applied Catalysis B: Environmental 2017 207:255–266 reports a cheap preparation of carbon ball-titanium dioxide composite visible light catalyst. The carbon ball structure is conducive to the close contact of the two components to form a doping energy level, thereby improving the photocatalytic level of the material. The invention patent with publication number CN110975852A provides a titanium dioxide nanocluster @ carbon ball multi-level composite structure material, using dichlorodipentadienyl titanocene as a titanium source, liquid linear carboxylic acid and liquid linear alkane as a mixed solvent, and preparing a titanium dioxide nanocluster @ carbon ball composite material through a solvent thermal reaction, and used for the treatment of organic wastewater. The invention patent with publication number CN107824174A discloses a titanium dioxide quantum dot / carbon ball composite material with a carbon ball synthesized from glucose as the core.
[0004] The specific surface area and porosity of the carbon ball material used in the above method are often low, which is not conducive to improving the adsorption effect of the composite material; in addition, the carbon ball material formed has a single elemental composition and lacks other heteroatom groups on the surface except for oxygen-containing groups, which limits the modification of the outer layer of nano-TiO2. The invention patent with publication number CN104607185A discloses a method for preparing a monodisperse spherical titanium dioxide core-shell structure composite material, and the noble metal metal ions are reduced to metal elements by hydrazine and attached to the surface of TiO2 to enhance the photocatalytic activity of the material. However, the process requires the addition of noble metal salts to complete the doping, which is costly and has many reaction steps. Summary of the invention
[0005] The invention provides a nano titanium dioxide / porous ball material and a preparation method and application thereof, which are used to improve the photocatalytic activity of titanium dioxide and reduce the preparation cost.
[0006] The first aspect of the present invention provides a method for preparing a nano titanium dioxide / porous carbon sphere material, comprising the following steps:
[0007] The iron salt and the carbohydrazide derivative are subjected to a coordination reaction, and then a polymerization reaction is carried out with furfural. The polymerization reaction temperature is 160-200° C. and the time is 9-12 hours. After the polymerization reaction is completed, a polymer precursor is obtained.
[0008] Under a protective gas atmosphere, the polymer precursor is carbonized at a temperature of 700-950° C. for 1-3 hours. After the carbonization is completed, a porous carbon ball material is obtained;
[0009] The porous carbon sphere material is dispersed in a solvent, and an organic titanium compound is added to carry out a solvothermal reaction. The temperature of the solvothermal reaction is 140-220° C., and the time is 3-10 hours. After the solvothermal reaction is completed, the nano titanium dioxide / porous carbon sphere material is obtained.
[0010] In a specific embodiment, the iron salt is one or more of iron halide, iron nitrate and iron sulfate.
[0011] In a specific embodiment, the carbohydrazide derivative is one or both of phenylaminourea and phenylaminothiourea.
[0012] In a specific embodiment, the mass ratio of the iron salt to the carbohydrazide derivative is 1:(1-8).
[0013] In a specific embodiment, based on the mass of the iron salt, the volume of furfural added is 2.5-10 mL for every 1 g of iron salt.
[0014] In a specific embodiment, the organic titanium compound is one or both of titanium isopropoxide and tetrabutyl titanate.
[0015] In a specific embodiment, based on the mass of the porous carbon sphere material, 0.1-1.2 mL of the organic titanium compound is added for every 6 mg of the porous carbon sphere material.
[0016] In a specific embodiment, the solvothermal reaction is carried out at a temperature of 160-200° C. and for a time of 4-6 hours.
[0017] The second aspect of the present invention provides a nano titanium dioxide / porous carbon sphere material prepared according to any of the above methods.
[0018] The third aspect of the present invention provides the use of the above-mentioned nano titanium dioxide / porous carbon sphere material in photocatalytic reactions.
[0019] The preparation method provided by the present invention can obtain anatase-type nano titanium dioxide with a high degree of crystallinity without secondary calcination, and realizes the co-doping of metal ions and non-metal ions to nano titanium dioxide without the need for dopants, thereby improving the visible light catalytic performance of the composite material; at the same time, the porous carbon ball material has excellent specific surface area and mesoporous structure, which helps to improve the enrichment capacity in the photocatalytic reaction process, and enhances the mass transfer of reactants and the conduction of photoelectrons, thereby improving the adsorption synergy performance of the composite material; the material prepared by the preparation method of the present invention can be used for light purification of water pollutants and atmospheric pollutants, and has good catalytic performance and stability in use, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0021] Figure 1 A schematic diagram of a preparation method according to an embodiment of the present invention;
[0022] Figure 2 Scanning electron microscope images of the porous carbon sphere material Fe / N-CS and the nano-titanium dioxide / porous carbon sphere material Fe / N-CST-3 provided in Example 1 of the present invention;
[0023] Figure 3 A transmission electron microscope image of the nano-titanium dioxide / porous carbon sphere material Fe / N-CST-3 provided in Example 1 of the present invention;
[0024] Figure 4 The XRD spectrum of the nano-titanium dioxide / porous carbon sphere material Fe / N-CST-3 provided in Example 1 of the present invention;
[0025] Figure 5 XPS test spectra of the nano-titanium dioxide / porous carbon sphere material Fe / N-CST-3, the porous carbon sphere material Fe / N-CS provided in Example 1 of the present invention and the p-TiO2 provided in Comparative Example 1;
[0026] Figure 6 The ultraviolet-visible diffuse reflectance spectra of the materials provided in Examples 1-3 and Comparative Examples 1-2 of the present invention;
[0027] Figure 7 The materials provided in Examples 1-3 and Comparative Examples 1-2 of the present invention have photocatalytic activity in degrading rhodamine B under visible light (>420 nm);
[0028] Figure 8 The reusability test results of the material provided in Example 1 of the present invention for degrading Rhodamine B;
[0029] Fig. 9 The materials provided in Examples 1-3 and Comparative Examples 1-2 of the present invention have photocatalytic activity in degrading p-xylene under irradiation with visible light (>420 nm). DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Figure 1 A schematic diagram of a preparation method according to an embodiment of the present invention is shown in FIG. Figure 1 As shown, the method specifically comprises the following steps:
[0032] Step 100, conducting a coordination reaction between an iron salt and a carbohydrazide derivative, and then conducting a polymerization reaction with furfural, wherein the polymerization reaction temperature is 160-200° C. and the time is 9-12 hours. After the polymerization reaction is completed, a polymer precursor is obtained;
[0033] It should be noted that the present invention limits the reaction sequence of the raw materials, that is, the iron salt and the carbohydrazide derivative are firstly subjected to a coordination reaction, and then the iron salt and the carbohydrazide derivative are subjected to a polymerization reaction. The present invention does not limit the order of adding the raw materials, that is, the iron salt and the carbohydrazide derivative can be first added to the solvent, stirred at room temperature for coordination reaction, and then the furfural is added, and the mixture is transferred to a reactor for polymerization reaction. Alternatively, the iron salt, the carbohydrazide derivative and the furfural can be added to the solvent at the same time, stirred at room temperature, during which only the iron salt and the carbohydrazide derivative are subjected to a coordination reaction, and then the mixed solution is transferred to a reactor for polymerization reaction to obtain a polymer precursor.
[0034] In a specific embodiment, the iron salt refers to one or more of iron halides, iron nitrates and iron sulfates that can react with carbohydrazide derivatives, for example, iron chloride, iron nitrate, iron sulfate, etc.; the carbohydrazide derivative refers to a more complex product derived from the replacement of hydrogen atoms, oxygen atoms or other atomic groups in carbohydrazide by other atoms or atomic groups, specifically one or two of phenylaminourea and phenylaminothiourea, the mass ratio of the iron salt to the carbohydrazide derivative is 1: (1-8), further, the mass ratio of the iron salt to the carbohydrazide derivative is 1: (2-4), by adjusting the mass ratio of the iron salt to the carbohydrazide derivative, the size and pore structure of the porous carbon sphere material can be effectively regulated.
[0035] During the preparation process, the iron salt and the carbohydrazide derivative can be first added to a solvent and stirred at room temperature for a coordination reaction. The solvent can be ethanol. The specific stirring time can be 1-2 hours. Based on the mass of the carbohydrazide derivative, 10-50 mL of ethanol is added for every 0.2 g of the carbohydrazide derivative. If too much solvent is added, the yield of the porous carbon sphere material will be affected. Furthermore, the volume of the ethanol is 20-30 mL.
[0036] Subsequently, furfural can be added, and the mixed solution is transferred to a reactor for polymerization reaction. Furfural has good solubility in solvents, and compared with other aldehydes, such as glutaraldehyde, salicylaldehyde, terephthalaldehyde, glyoxal, etc., furfural can ensure the spherical shape of the final carbon ball material. In order to further improve the catalytic performance, based on the mass of the iron salt, the volume of furfural added is 2.5-10mL for every 1g of iron salt.
[0037] The polymerization reaction temperature is 160-200° C., and the time is 9-12 hours. After the polymerization reaction is completed, the reaction product is washed, centrifuged, and dried to obtain a polymer precursor.
[0038] Step 200, in a protective gas atmosphere, the polymer precursor is subjected to a carbonization treatment at a temperature of 700-950° C. for 1-3 hours. After the carbonization treatment is completed, a porous carbon ball material is obtained;
[0039] The polymer precursor prepared in step 100 is a solid spherical structure. The polymer precursor needs to be carbonized. During the carbonization process, the excessive nitrogen-containing groups are incompletely decomposed to promote the formation of pores. At the same time, the coordination structure of iron and nitrogen atoms can in situ introduce Fe-N with high catalytic activity. x Active sites are formed to form porous carbon sphere materials with open pore structures, and the electrocatalytic performance of the porous carbon sphere materials is improved.
[0040] The temperature of the carbonization treatment is 700-950°C, and the time is 1-3h. Furthermore, the temperature of the carbonization treatment is 700-900°C, which helps to ensure that the spherical structure is not easy to collapse and further improve the porosity of the porous carbon sphere material.
[0041] Step 300, dispersing the porous carbon sphere material in a solvent, adding an organic titanium compound to carry out a solvothermal reaction, wherein the solvothermal reaction temperature is 140-220° C., and the time is 3-10 hours. After the solvothermal reaction is completed, the nano titanium dioxide / porous carbon sphere material is obtained;
[0042] The porous carbon sphere material prepared in step 200 is dispersed in a solvent, specifically an alcohol solvent such as ethanol, and an organic titanium compound is added. The organic titanium compound refers to an organic compound including a titanium atom in its molecular structure, such as one or both of titanium isopropoxide and tetrabutyl titanate.
[0043] Research has found that the mass ratio of porous carbon sphere material to organic titanium compound affects the catalytic performance of the final composite material. Specifically, based on the mass of the porous carbon sphere material, 0.1-1.2 mL of organic titanium compound is added for every 6 mg of porous carbon sphere material. Furthermore, 0.1-0.6 mL of organic titanium compound is added for every 6 mg of porous carbon sphere material.
[0044] Subsequently, the reaction temperature is controlled at 140-220°C for a solvothermal reaction. During the solvothermal reaction, the organic titanium compound grows into anatase-type nano-titanium dioxide on the surface of the porous carbon sphere material, and the Fe and N groups on the surface of the porous carbon sphere material are doped into the nano-titanium dioxide lattice in the form of ions, realizing the co-doping of titanium dioxide with metal ions and non-metal ions, thereby improving the photocatalytic performance of the material. Furthermore, the temperature of the solvothermal reaction is 160-200°C, and the time is 4-6 hours.
[0045] After the solvent thermal reaction is completed, the reaction product can be washed, centrifuged and dried to obtain a composite material. The composite material has a porous carbon ball material as the core and Fe, N dual-doped nano-titanium dioxide as the shell. It can be used for visible light catalytic oxidation degradation of water pollutants and atmospheric pollutants. The diameter of the core porous carbon ball material is 2-4μm, and the shell thickness is 50-250nm. Furthermore, the shell thickness is 50-100nm, the proportion of TiO2 is 72-96wt%, and the proportion of carbon element is 2-15wt%.
[0046] In summary, the preparation method provided by the present invention can obtain anatase-type nano-titanium dioxide with a high degree of crystallinity without secondary calcination, and realizes the co-doping of nano-titanium dioxide with metal ions and non-metal ions without the need for dopants, thereby improving the visible light catalytic performance of the composite material; at the same time, the porous carbon ball material has excellent specific surface area and mesoporous structure, which helps to improve the enrichment capacity in the photocatalytic reaction process, enhance the mass transfer of reactants and the conduction of photoelectrons, thereby improving the adsorption synergy of the composite material; the material prepared by the preparation method of the present invention can be used for the treatment of water pollutants and atmospheric pollutants, and has good catalytic performance and stability in use, and has good application prospects.
[0047] The present invention is further described below in conjunction with specific embodiments:
[0048] Example 1
[0049] This embodiment provides a method for preparing a nano titanium dioxide / porous carbon sphere material:
[0050] Step 1, 0.1g of iron salt, 0.4g of dibenzoyl hydrazide and 500μL of furfural were mixed and stirred thoroughly. After the stirring was completed, the mixed solution was placed in a reactor and subjected to polymerization reaction at 180°C for 9h. After the reaction was completed, a polymer precursor was obtained;
[0051] Step 2: In a protective gas atmosphere, the polymer precursor is carbonized at a temperature of 900° C. for 2 hours. After the carbonization treatment, a porous carbon sphere material is obtained, named Fe / N-CS.
[0052] Step 3: Disperse 6 mg of porous carbon sphere material Fe / N-CS in ethanol solvent, add 0.2 ml of tetrabutyl titanate, and carry out solvent thermal reaction at 180°C for 5 hours. After the reaction, wash, centrifuge and dry to obtain nano titanium dioxide / porous carbon sphere material, named Fe / N-CST-3.
[0053] Physical adsorption test was performed on Fe / N-CST-3, and the specific surface area of the material was 141m 2 / g, and the total pore volume is 0.38cm3 / g, of which the mesopore area is 137m 2 / g, indicating that the material is mainly composed of mesopores.
[0054] The element content of Fe / N-CST-3 material was tested, wherein the relative content of TiO2 was 82.1%, the relative content of carbon phase was 7.1%, the nitrogen doping amount was 0.51%, the iron doping amount was 0.29%, and the remainder was oxygen and hydrogen elements as well as necessary test errors.
[0055] Figure 2 The scanning electron microscope images of the porous carbon sphere material Fe / N-CS and the nano-titanium dioxide / porous carbon sphere material Fe / N-CST-3 provided in Example 1 of the present invention, wherein (a) is a scanning electron microscope image of the porous carbon sphere material Fe / N-CS at 1 μm, (b) is a scanning electron microscope image of the porous carbon sphere material Fe / N-CS at 200 nm, (c) is a scanning electron microscope image of the nano-titanium dioxide / porous carbon sphere material Fe / N-CST-3 at 1 μm, and (d) is a scanning electron microscope image of the nano-titanium dioxide / porous carbon sphere material Fe / N-CST-3 at 200 nm, as shown in FIG. Figure 2 As shown in the figure, the diameter of the porous carbon sphere material Fe / N-CS is about 3μm, and there are a large number of holes on its surface, especially the inside of the sphere also presents a loose porous structure. This loose porous structure can greatly increase the specific surface area of the overall material, and can effectively enrich and increase the adsorption amount of pollutants during the adsorption and photocatalytic process. At the same time, the physical adsorption test results show that the mesopore area is 137m 2 / g, the open structure with densely distributed mesopores is conducive to the mass transfer of pollutants in the material and improves the photocatalytic efficiency. In addition, since the surface of the porous carbon ball material Fe / N-CS is relatively rough, after the solvent thermal reaction with organic titanium, it is conducive to the attachment of nano-titanium dioxide, and the formed nano-TiO2 particles are fully wrapped on the surface of the Fe / N-CS sphere to form a nano-titanium dioxide / porous carbon ball material with a core-shell structure, which optimizes the dispersion of nano-TiO2 and reduces its agglomeration. At the same time, it effectively increases the contact area between TiO2 and visible light and improves the light utilization rate.
[0056] Figure 3 The transmission electron microscope image of the nano-titanium dioxide / porous carbon ball material Fe / N-CST-3 provided in Example 1 of the present invention is as follows: Figure 3 As shown, transmission electron microscopy further proves that the material has a core-shell structure. The nano-titanium dioxide generated during the solvothermal reaction is wrapped around the outer surface of the porous carbon ball material to form a shell with a thickness of about 50-200nm. The particle size of the formed nano-titanium dioxide particles is about 15nm, which is larger than the particle size of the nano-titanium dioxide (p-TiO2) synthesized in Comparative Example 1.
[0057] Figure 4 The XRD spectrum of the nano-titanium dioxide / porous carbon ball material Fe / N-CST-3 provided in Example 1 of the present invention is as follows: Figure 4 As shown, the diffraction peaks at 25.3°, 38.0°, 48.0°, 54.0° and 55.1° correspond to the (101), (004), (200), (105) and (211) crystal planes of anatase titanium dioxide (JCPDS No. 21-1272), respectively, indicating that the preparation method provided in this embodiment can obtain anatase titanium dioxide with a high degree of crystallinity without the need for a secondary roasting process.
[0058] Example 2
[0059] The preparation method of the nano-titanium dioxide / porous carbon sphere material provided in this embodiment can refer to Example 1, except that:
[0060] Step 3: Disperse 6 mg of porous carbon sphere material Fe / N-CS in ethanol solvent, add 0.1 ml of tetrabutyl titanate, and carry out solvent thermal reaction at 180°C for 5 hours. After the reaction, wash, centrifuge and dry to obtain nano-titanium dioxide / porous carbon sphere material, named Fe / N-CST-6.
[0061] Physical adsorption test was performed on Fe / N-CST-6, and the specific surface area of the material was 174m 2 / g, and the total pore volume is 0.44cm 3 / g, of which the mesopore area is 152m 2 / g.
[0062] The element content of Fe / N-CST-6 was tested, wherein the relative content of TiO2 was 76.2%, the relative content of carbon was 13.0%, the nitrogen doping amount was 0.84%, the iron doping amount was 0.56%, and the remainder was oxygen and hydrogen elements as well as necessary test errors.
[0063] Example 3
[0064] The preparation method of the nano-titanium dioxide / porous carbon sphere material provided in this embodiment can refer to Example 1, except that:
[0065] Step 3: Disperse 6 mg of porous carbon sphere material Fe / N-CS in ethanol solvent, add 0.4 ml of tetrabutyl titanate, and carry out solvent thermal reaction at 180°C for 5 hours. After the reaction, wash, centrifuge and dry to obtain nano titanium dioxide / porous carbon sphere material, named Fe / N-CST-1.5.
[0066] Physical adsorption test was performed on Fe / N-CST-1.5, and the specific surface area of the material was 123m 2 / g, the total pore volume is 0.30cm 3 / g, of which the mesopore area is 111m 2 / g.
[0067] The element content of Fe / N-CST-1.5 was tested, wherein the relative content of TiO2 was 89.8%, the relative content of carbon was 4.9%, the nitrogen doping amount was 0.28%, the iron doping amount was 0.22%, and the remainder was oxygen and hydrogen elements as well as necessary test errors.
[0068] Comparative Example 1
[0069] The materials provided in this comparative example do not include porous carbon ball materials. The specific steps are to disperse 0.2 mL of tetrabutyl titanate in ethanol solvent, and perform solvent thermal reaction at 180°C for 5 hours. After the reaction, the nano titanium dioxide catalyst is obtained after washing, centrifugation and drying, and is named p-TiO2.
[0070] The physical adsorption test of p-TiO2 was carried out and the specific surface area of the material was 117m 2 / g, with a total pore volume of 0.21 cm 3 / g, of which the mesopore area is 108m 2 / g.
[0071] Comparative Example 2
[0072] A commercial titanium dioxide catalyst (P25, purchased from Aladdin Reagents) was used as a comparison.
[0073] Physical adsorption test was performed on P25, which has a specific surface area of 50m 2 / g, and the total pore volume is 0.11cm 3 / g, of which the mesopore area is 40m 2 / g.
[0074] The present invention lists the specific surface area, mesopore area and pore volume of the materials used in Examples 1-3 and Comparative Examples 1-2, as shown in Table 1:
[0075] Table 1 shows the pore structure parameters of the materials provided in Examples 1-3 and Comparative Examples 1-2
[0076]
[0077] According to Table 1, the specific surface area of the commercial P25 photocatalyst is small and the porosity is extremely low. Compared with the commercial P25, the specific surface area and porosity of the p-TiO2 catalyst provided in Comparative Example 1 are doubled, which is due to the smaller p-TiO2 nanoparticle size, resulting in an increase in the specific surface area. Compared with Comparative Examples 1-2, the specific surface area and pore volume of the composite materials provided in Examples 1-3 increase successively with the increase of the porous carbon component, and the number and size of the mesopores increase significantly, which is not only conducive to the adsorption and enrichment of pollutant molecules on the material, but also the suitable pore structure can promote the mass transfer of pollutants, thereby improving the catalytic rate of the material in the photocatalytic reaction process.
[0078] Figure 5 The XPS test spectra of the nano-titanium dioxide / porous carbon sphere material Fe / N-CST-3, the porous carbon sphere material Fe / N-CS and the p-TiO2 provided in Example 1 of the present invention, wherein (a) the upper part is the Ti 2p test spectrum of the p-TiO2 provided in Comparative Example 1, and the lower part is the Ti 2p test spectrum of the nano-titanium dioxide / porous carbon sphere material Fe / N-CST-3 provided in Example 1, (b) the upper part is the O1s test spectrum of the p-TiO2 provided in Comparative Example 1, and the lower part is the O1s test spectrum of the nano-titanium dioxide / porous carbon sphere material Fe / N-CST-3 provided in Example 1, (c) the upper part is the N1s test spectrum of the porous carbon sphere material Fe / N-CS provided in step 2 of Example 1, and the lower part is the N1s test spectrum of the nano-titanium dioxide / porous carbon sphere material Fe / N-CST-3 provided in Example 1, as shown in FIG. Figure 5 As shown in (a), Ti in p-TiO2 4+ The corresponding Ti 2p 1 / 2 and Ti 2p 3 / 2 The binding energies of the peaks are 463.5 and 457.8 eV, respectively. 4+ The corresponding peak also shows Ti 3+ Corresponding to Ti2p 1 / 2 (364.5 eV) and Ti 2p 3 / 2 (358.5eV), we speculate that Ti 3+ The appearance of may be due to the reaction between the Fe and N atoms on the surface of the carbon sphere and the Ti 4+ A reduction reaction occurs and enters the TiO2 lattice to achieve doping. This doping method of introducing oxygen vacancies and trivalent titanium into titanium dioxide can overcome the shortcomings of traditional white titanium dioxide, reduce the band gap width of TiO2 and reduce the electron / hole recombination rate during the photocatalytic reaction.
[0079] according to Figure 5As can be seen in (b), compared with p-TiO2, a new peak appears at 534.0 eV in the O1s XPS spectrum of Fe / N-CST-3, which belongs to the CO-Ti structure. This proves that the formed nano-TiO2 is bonded to the surface of the carbon sphere. In addition, the binding energy of the spin-orbit splitting of Ti 2p and O1s in the Fe / N-CST-3 material is enhanced compared with that of p-TiO2, which may be attributed to the doping of Fe and N in the titanium dioxide lattice or the formation of oxygen vacancies.
[0080] like Figure 5 As shown in (c), the peaks in the N1s XPS spectrum of the Fe / N-CS carbon ball material represent the quaternary nitrogen (N-5) and quaternary nitrogen (QN) doped in the carbon ball material. After forming the composite material, the bonding form of the N atoms in the Fe / N-CST-3 material changes greatly. The new peak at a lower binding energy of 396 eV may be due to the formation of O-Ti-N by N- anion doping in TiO2; the peak at a higher binding energy of 402 eV may be the oxidized nitrogen group (NO x ) or Ti-NO or Ti-ON formed in the gaps of nano-TiO2, both of which prove that N atoms are doped into nano-TiO2.
[0081] The catalytic performance of semiconductor photocatalysts is related to their light absorption capacity and the separation efficiency of photogenerated electrons and holes. The light absorption properties of the materials are tested and their bandgap width is calculated by UV-visible diffuse reflectance spectroscopy. Figure 6 The UV-visible diffuse reflectance spectra of the materials provided in Examples 1-3 and Comparative Examples 1-2 of the present invention are as follows: Figure 6 As shown, the P25 and p-TiO2 materials provided in Comparative Examples 1-2 can only absorb ultraviolet light, and have no absorption above 380nm, while the light absorption of the composite materials provided in Examples 1-3 can be extended to visible light, and as the proportion of porous carbon ball material in the composite material increases, not only the apparent material color deepens, but also the absorption in the visible light region of 400-750nm gradually increases.
[0082] The energy band gap of the material is calculated by boundary absorption. The band gap of p-TiO2 is slightly smaller than that of P25 (3.28 eV). The band gap of the composite material decreases with the increase of the porous carbon component. This shows that the porous carbon ball material and nano-titanium dioxide are not a simple combination, but the interface effect and doping effect produce the narrowing of the material energy band gap, which is beneficial to the absorption of visible light.
[0083] The photocatalytic oxidation experiment of water pollutant Rhodamine B was carried out using the materials provided in Examples 1-3 and Comparative Examples 1-2. The experimental process includes: adding 25 mg of the material to be tested to 50 mL of an aqueous solution containing 10 mg / L Rhodamine B, maintaining the reaction temperature at 25°C, and stirring continuously for 40 minutes in a dark environment to achieve adsorption equilibrium. Then, a photocatalytic experiment was carried out using a 300W xenon lamp (equipped with a 420nm cut-off filter) as the light source. After a period of time, 2.0 mL of the solution was taken and filtered with a 0.45μm microporous membrane, and the absorbance was measured by a UV-visible spectrophotometer.
[0084] Figure 7 The materials provided in Examples 1-3 and Comparative Examples 1-2 of the present invention have photocatalytic activity in degrading rhodamine B under visible light (>420 nm), such as Figure 7 As shown, Comparative Example 2 is a commercial P25 material, which has a very small specific surface area and weak adsorption performance, with an adsorption capacity of only 7.1%. The p-TiO2 provided in Comparative Example 1 has an increased specific surface area due to a reduced particle size and an increased number of surface functional groups, and its adsorption capacity increases to 22.1%; the adsorption capacities of the composite materials provided in Examples 1-3 are all higher than those of Comparative Examples 1-2, and the increased proportion of porous carbon balls in the composite materials is beneficial to a higher dark adsorption efficiency, among which the dark adsorption capacity of Fe / N-CST-3 can reach 39.6%.
[0085] The photocatalytic degradation experiment was carried out under visible light. After 60 minutes of reaction, the catalytic degradation rates of P25, p-TiO2 and Fe / N-CST-3 materials were 28.3%, 57.4% and 96.2%, respectively. The catalytic effect of other Fe / N-CST-x materials was also higher than that of p-TiO2, indicating that the visible light catalytic performance of the composite material in the solution environment can be greatly improved by using doped porous carbon spheres as the loading substrate. In addition, as the titanium dioxide loading increases within a certain range, the photoelectron-hole excited by visible light increases, and the degradation rate increases accordingly. However, when there are too many porous carbon spheres, the generated titanium dioxide is not enough to completely cover the surface of the carbon spheres, resulting in a decrease in the photocatalytic effect.
[0086] Next, the durability of the composite material provided in Example 1 for the photocatalytic degradation of Rhodamine B was tested. Figure 8 The reusability test results of the material degradation of Rhodamine B provided in Example 1 of the present invention are as follows: Figure 8 As shown, after multiple photocatalytic degradation experiments, the catalytic material can maintain stable photocatalytic performance, and the degradation rate of Rhodamine B can still be maintained at more than 97%, indicating that the material has good stability and durability in use.
[0087] The materials provided in Examples 1-3 and Comparative Examples 1-2 were used to carry out a photocatalytic oxidation experiment of the atmospheric pollutant p-xylene. The experimental method includes: dissolving 50 mg of the material to be tested in 1 mL of ethanol and ultrasonically forming a homogenate, then dripping the homogenate onto a quartz sheet one by one, drying it for later use; the volume of the quartz reactor is 100 mL, and a glass sheet is placed in the middle of the container; a 300 W xenon lamp (equipped with a 420 nm cut-off filter) is used as a reaction light source, and the light intensity density is about 200 mW / cm 2 Directly introduce 100 ppm of p-xylene gas into the reaction bottle through a gas cylinder, close the inlet and outlet valves, keep the material statically adsorbed for 30 minutes, and then start the photocatalytic experiment. Take 1 mL of sample at regular intervals and detect the concentration of remaining p-xylene by gas chromatography.
[0088] Fig. 9 The photocatalytic activity of the materials provided in Examples 1-3 and Comparative Examples 1-2 in the degradation of p-xylene under visible light (>420 nm) is as follows: Fig. 9 As shown, the adsorption capacity of the composite materials provided by Examples 1-3 is better than that of Comparative Examples 1-2; when irradiated with visible light, the concentration of p-xylene continues to decrease under the catalysis of the composite materials provided by Examples 1-3. This is because the p-xylene adsorbed in the porous material can be quickly transferred to the surface of the photoactive nano-titanium dioxide in the photocatalytic reaction to complete the catalytic decomposition, and at the same time the pores are regenerated to carry out a new adsorption transfer process. Among them, the degradation rate of p-xylene of Fe / N-CST-3 reaches 94.1% after 20 minutes of photocatalysis, and reaches 98.7% after 60 minutes of reaction, indicating that the material also has good visible light catalytic performance for gaseous p-xylene pollutants.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing nano titanium dioxide / porous carbon sphere material, characterized in that: The steps include: The iron salt and the carbohydrazide derivative are subjected to a coordination reaction, and then a polymerization reaction is carried out with furfural. The polymerization reaction temperature is 160-200°C and the time is 9-12 hours. After the polymerization reaction is completed, a polymer precursor is obtained. The carbohydrazide derivative is one or two of phenylaminourea and phenylaminothiourea. The polymer precursor is subjected to carbonization treatment under a protective gas atmosphere, wherein the temperature of the carbonization treatment is 700-950° C. and the time is 1-3 h. After the carbonization treatment is completed, a porous carbon ball material is obtained; The porous carbon sphere material is dispersed in a solvent, and an organic titanium compound is added to carry out a solvothermal reaction. The temperature of the solvothermal reaction is 140-220°C, and the time is 3-10 hours. After the solvothermal reaction is completed, the nano titanium dioxide / porous carbon sphere material is obtained. Based on the mass of the porous carbon sphere material, 0.1-1.2 mL of the organic titanium compound is added for every 6 mg of the porous carbon sphere material.
2. The preparation method according to claim 1, characterized in that: The iron salt is one or more of iron halide, iron nitrate and iron sulfate.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the iron salt to the carbohydrazide derivative is 1:(1-8).
4. The preparation method according to claim 1 or 2, characterized in that: Based on the mass of the iron salt, the volume of furfural added is 2.5-10 mL for every 1 g of iron salt.
5. The preparation method according to claim 1, characterized in that: The organic titanium compound is one or both of titanium isopropoxide and tetrabutyl titanate.
6. The preparation method according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 160-200° C. and the time is 4-6 hours.
7. A nano titanium dioxide / porous carbon sphere material, characterized in that: Prepared according to the method according to any one of claims 1 to 6.
8. Use of the nano-titanium dioxide / porous carbon sphere material according to claim 7 in visible light catalytic reaction.
Citation Information
Patent Citations
Monodispersed spherical titanium dioxide core-shell structure composite material and preparation method thereof
CN104607185A
Titanium dioxide quantum dot / carbon sphere composite and preparation method thereof
CN107824174A
Titanium dioxide nano-cluster@carbon sphere multistage composite structure material as well as preparation method and application thereof
CN110975852A